Investigation of toxic components of hookah mixture aerosol - N. N. Matyukhina; A. S. Podvysotsky; M. V. Shkidyuk (Новые технологии, 2017)
As a result of the studies, the main factors influencing the toxicity of the aerosol formed during the smoking of hookah mixture were determined. Dependence of aerosol toxicity indicators on the chemical composition and content of tobacco raw materials in hookah mixtures was established.